The Bible and the justification of apartheid in Reformed circles in the 1940's in South Africa: Some historical, hermeneutical and theological remarks - Vosloo, Robert (Stellenbosch theological journal, 2015)
This article focuses on the way the Bible was used in the 1940s in some Reformed theological circles in South Africa as part of the discourse to justify apartheid. Attention is also given to some voices critical of this endeavour. The article therefore offers a close reading of influential texts by prominent theologians who provided a biblical justification of apartheid, such as JD du Toit (Totius) and EP Groenewald. In addition, the article attends to some of the writings of theologians such as BJ Marais and BB Keet, who strongly opposed any attempt to justify apartheid in this manner. The article is especially interested in identifying the constructions of identity and otherness that seem to be operative in the discourse connected to the biblical justification of apartheid during this period.